Fluidized Bed Reactors for Carbon Capture - Duan, Lunbo; Lu, Dennis (Springer Nature, 2025)
This open access book provides a perspective on CO2 capture technologies that employ fluidized bed rectors, (FBRs) involving pre-combustion gasification, oxy-fuel combustion, chemical looping combustion, calcium looping process, and low-temperature sorption. The state-of-the-art progress from the lab-scale FBRs to pilot-scale demonstration facilities is summarized, and the remaining challenges are discussed. Moreover, this book also discussed the future solutions to overcome existing barriers in the application of FBRs for CO2 capture and provided an outlook on potential advancements and improvements. The authors anticipate endeavors made herein can impel the commercialization of fluidized bed technologies for CO2 capture from large industrial sources.